2020
DOI: 10.1093/nar/gkaa871
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of chromosomes:in vivoandin silicoapproaches reveal high-level organization and structure arise exclusively through mechanical feedback between loop extruders and chromatin substrate properties

Abstract: The revolution in understanding higher order chromosome dynamics and organization derives from treating the chromosome as a chain polymer and adapting appropriate polymer-based physical principles. Using basic principles, such as entropic fluctuations and timescales of relaxation of Rouse polymer chains, one can recapitulate the dominant features of chromatin motion observed in vivo. An emerging challenge is to relate the mechanical properties of chromatin to more nuanced organizational principles such as ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
(57 reference statements)
3
20
0
Order By: Relevance
“…ranging from seconds to minutes). More detailed molecular models provide additional information regarding local structure dynamics and have addressed chromosomal features including loop extrusion and heterogeneous properties (74), centromere tethering (75), and chromosomal crosslinking (76). Our approach complements these detailed models by predicting large-scale chromosomal dynamics and including influences from some of these detailed effects.…”
Section: Resultsmentioning
confidence: 99%
“…ranging from seconds to minutes). More detailed molecular models provide additional information regarding local structure dynamics and have addressed chromosomal features including loop extrusion and heterogeneous properties (74), centromere tethering (75), and chromosomal crosslinking (76). Our approach complements these detailed models by predicting large-scale chromosomal dynamics and including influences from some of these detailed effects.…”
Section: Resultsmentioning
confidence: 99%
“…The most extreme case of histone regulation is the degradation of histone protein following DNA damage, as a driver of increased chromatin motility [ 82 , 83 ]. To better understand the consequences of histone depletion from the perspective of the DNA chain, we have introduced histones and their dynamic turnover into the fluctuating bead–spring chains [ 57 , 84 ]. Using in vivo and in silico approaches we found that both histones and condensin cross-linkers were required in silico in order to quantitatively match the dynamic chromatin compaction observed in vivo [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the consequences of histone depletion from the perspective of the DNA chain, we have introduced histones and their dynamic turnover into the fluctuating bead–spring chains [ 57 , 84 ]. Using in vivo and in silico approaches we found that both histones and condensin cross-linkers were required in silico in order to quantitatively match the dynamic chromatin compaction observed in vivo [ 57 ]. An exact experimental correlate of our bead–spring simulation was obtained through analysis of a model-matching, fluorescently labeled, circular chromosome in live yeast cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations